Pengaruh teknik guided imagery terhadap penurunan nyeri dismenore pada remaja putri di SMA Pringsewu - Desi Ari Madiyanti; Marlinda Marlinda; Dewi Okta Periyanti (Holistik Jurnal Kesehatan, 2024)
Background: Menstruation is periodic bleeding from the uterus that begins approximately 14 days after ovulation periodically due to the shedding of the endometrial lining of the uterus. Physical discomfort during menstruation is called dysmenorrhea. Several actions can be taken to reduce dysmenorrhea, such as taking anti-pain medication or warm compresses. Purpose: To determine the effect of guided imagery techniques on dysmenorrhea pain in adolescent girls. Method: This type of quasi-experimental research with a pre-post-test non-equivalent control group approach. The sample of 36 female students was divided into 2 groups, 18 samples in the intervention group and 18 samples in the control group using consecutive sampling. The research instruments were a numeric rating scale (NRS) observation sheet and a standard operating procedure guided imagery. Data were analyzed using the Mann Whitney test. Results: The average age of female adolescent students who experienced dysmenorrhea in the intervention group was 16 years with a minimum age of 15 years and a maximum of 16 years. In the control group, the average age of young female students who experienced dysmenorrhea was 16 years with a minimum age of 15 years and a maximum of 18 years. The average pain in the intervention group before intervention was 6.78 and after intervention 1.94. Conclusion: This research shows that there is an effect of guided imagery techniques on reducing dysmenorrhea pain in young women with a p-value of 0.013 <0.05.   Keywords: Dysmenorrhea; Guided Imagery Therapy; Menstruation.   Pendahuluan: Menstruasi merupakan perdarahan periodik dari rahim yang dimulai sekitar 14 hari setelah ovulasi secara berkala akibat terlepasnya lapisan endometrium uterus. Ketidaknyamanan fisik saat menstruasi disebut dismenore. Beberapa tindakan dapat dilakukan untuk mengurangi dismenore seperti minum obat anti nyeri atau kompres hangat. Tujuan: Untuk mengetahui pengaruh teknik guided imagery terhadap nyeri dismenore pada remaja putri. Metode: Jenis penelitian quasi eksperimen dengan pendekatan pre-post-test non-equivalent control group. Sampel sebanyak 36 siswi terbagi menjadi 2 kelompok, 18 sampel kelompok intervensi dan 18 sampel kelompok kontrol dengan consecutive sampling. Instrumen penelitian berupa lembar observasi numeric rating scale (NRS) dan standar operasi prosedur (SOP) guided imagery. Data dianalisis menggunakan uji mann whitney. Hasil: Rata-rata usia siswi remaja putri yang mengalami dismenore pada kelompok intervensi adalah 16 tahun dengan usia minimal 15 tahun dan maksimal 16 tahun. Pada kelompok kontrol rata-rata usia siswi remaja putri yang mengalami dismenore adalah 16 tahun dengan usia minimal 15 tahun dan maksimal 18 tahun. Rata-rata nyeri pada kelompok intervensi sebelum intervensi 6.78 dan sesudah intervensi 1.94. Simpulan: Penelitian ini menunjukkan bahwa ada pengaruh teknik guided imagery terhadap penurunan nyeri dismenore pada remaja putri dengan nilai p-value 0.013 <0.05.   Kata Kunci: Dismenore; Menstruasi; Terapi Guided Imagery.